2013
DOI: 10.2990/32_2_100
|View full text |Cite
|
Sign up to set email alerts
|

Framing of AIDS in Africa: Press-state relations, HIV/AIDS news, and journalistic advocacy in four sub-Saharan Anglophone newspapers

Abstract: This study offers the first systematic analysis of the impact of press-state relations, or media systems, on the HIV/AIDS news agenda in African news coverage. The premise is that media systems play a determining role in the degree to which journalists can independently advocate for social change when covering HIV/AIDS. Drawing on comparative research, four sub-Saharan countries were categorized into two media systems: Contained Democratic (South Africa, Nigeria) and Repressive Autocratic (Zimbabwe, Kenya). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…The cross-cutting impact of HIV has facilitated involvement, with sectors recognising that each has a role in the response to HIV. As observed by others, framing of the problem or the issue of HIV, in our study, from a developmental perspective was a critical step in bringing in non-health sectors to be actively involved in the response to HIV (Clark, 2006;D'Angelo, Pollock, Kiernicki, & Shaw, 2013). Non-health sector departments were able to locate themselves, addressing the social and structural drivers of the HIV epidemic in line with their main responsibility and function.…”
Section: Discussionsupporting
confidence: 54%
“…The cross-cutting impact of HIV has facilitated involvement, with sectors recognising that each has a role in the response to HIV. As observed by others, framing of the problem or the issue of HIV, in our study, from a developmental perspective was a critical step in bringing in non-health sectors to be actively involved in the response to HIV (Clark, 2006;D'Angelo, Pollock, Kiernicki, & Shaw, 2013). Non-health sector departments were able to locate themselves, addressing the social and structural drivers of the HIV epidemic in line with their main responsibility and function.…”
Section: Discussionsupporting
confidence: 54%
“…D’Angelo et al (2013) also delineated media systems found in sub-Saharan African countries and argued that the media system found in this region of the global south is a variation of the Polarized Pluralist system found in Mediterranean countries. According to D’Angelo and his colleagues, this system is marked by high political parallelism and external pluralism and instrumentalized advocacy.…”
Section: Media Systems Frameworkmentioning
confidence: 95%
“…To this end, I analysed newspaper articles from national newspapers from three West African countries (Nigeria, Sierra Leone and Liberia). These three countries represent the Polarized Pluralist media system according to D’Angelo et al’s (2013) modified version of the Hallin and Mancini (2004) model. I also analysed newspaper articles from the United States and the United Kingdom to represent the Liberal model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reveals that the higher the percentage of particular issue stakeholders in a community, the more likely newspaper coverage will report favorably on their interests (McLeod & Hertog, 1999; Pollock, 2007). For example, an examination of sub-Saharan Anglophone African newspaper coverage of AIDS found that a higher proportion of AIDs victims within a nation paralleled a greater media support for government intervention to fight the crisis (D’Angelo, Pollock, Kiernicki, & Shaw, 2013).…”
Section: Hypothesesmentioning
confidence: 99%